1980
DOI: 10.1073/pnas.77.6.3710
|View full text |Cite
|
Sign up to set email alerts
|

Slow reacting substances of anaphylaxis: Identification of leukotrienes C-1 and D from human and rat sources

Abstract: Slow reacting substance(s) of anaphylaxis (SRS-A) was isolated from both human (lung) and rat sources and compared with three synthetic SRS-As of known structureleukotrienes (LTs) C-1, C-2, and D. Reversed-phase liquid chromatography was used both as a final purification step and a means of comparison of biologically derived and synthetic substances. Two major peaks of SRS-A activity of both rat and human origin corresponded chromatographically with LTC-1 and LTD, respectively, and had equivalent specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
103
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(107 citation statements)
references
References 24 publications
3
103
1
Order By: Relevance
“…(20). After the structure elucidation of SRS-A (21,22), it was found that antigen challenge released LTC4 and LTD4 from passively sensitized human lung fragments (23) and that LTD4 was generated by immunological challenge of actively sensitized guinea pig lung (24). Since then, it has become evident that LTC4 is the primary SRS-A released and that further metabolism converts it into LTD4 and LTE4 (cf.…”
Section: Resultsmentioning
confidence: 99%
“…(20). After the structure elucidation of SRS-A (21,22), it was found that antigen challenge released LTC4 and LTD4 from passively sensitized human lung fragments (23) and that LTD4 was generated by immunological challenge of actively sensitized guinea pig lung (24). Since then, it has become evident that LTC4 is the primary SRS-A released and that further metabolism converts it into LTD4 and LTE4 (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Nedocromil is generally more effective at relieving asthma symptoms than cromolyn and may reduce the amount of inhaled steroids used in certain asthmatic patients. 18 While the efficacy of these agents in treating asthma appears to be less than the b 2 agonists and inhaled corticosteroids, both drugs have excellent track records of safety and few side effects due to their limited solubility.…”
Section: Course Contentmentioning
confidence: 99%
“…Both LTC and LTD have been shown to be produced by rat peritoneal macrophages when treated with a Ca2+ ionophore (Bach, Brashler, Hammarstrom & Samuelsson, 1980;Lewis, Austen, Drazen, Clark, Marfat & Corey, 1980). Furthermore, LTC has also been shown to be produced by mouse peritoneal macrophages in response to a phagocytotic stimulus (Rouzer, Scott, Cohn, Blackburn & Manning, 1980).…”
mentioning
confidence: 99%
“…Both LTC and LTD had been shown to be produced by rat macrophages upon stimulation with a Ca21 ionophore (Bach et al, 1980Lewis et al, 1980 and a phagocytotic stimulus (Rouzer et al, 1980). Furthermore, the importance of endogenous leukotrienes in mediating biological functioning of immunoreactive cells is suggested by a recent study which showed that lysosomal enzyme release from neutrophils induced by arachidonic acid was blocked by an inhibitor of the lipoxygenase pathway (Walenga, Showell, Feinsten & Becker, 1980 been shown to induce degranulation (lysosyme release) in human neutrophils (Stenson & Parker, 1980).…”
mentioning
confidence: 99%